Designing 1, 5‐Naphthyridine‐2, 6‐dione‐Based Conjugated Polymers for Higher Crystallinity and Enhanced Light Absorption to Achieve 9.63% Efficiency Polymer Solar Cells. Issue 2 (11th September 2017) - Yoon, Won Sik; Kim, Dong Won; Choi, Min‐Woo; Park, Jun‐Mo; Park, Soo Young
Abstract: Highly crystalline conjugated polymers represent a key material for producing high‐performance thick‐active‐layer polymer solar cells (PSCs). However, despite their potential, a limited number of crystalline polymers are used in PSCs because of the lack of highly coplanar acceptor building blocks and insufficient light absorptivity (α < 10 5 ) of most donor (D)–acceptor (A)‐type polymers. This study reports a series of novel 3, 7‐di(thiophen‐2‐yl)‐1, 5‐naphthyridine‐2, 6‐dione (NTDT) acceptor‐based conjugated polymers, PNTDT‐2T, PNTDT‐TT, and PNTDT‐2F2T, synthesized with 2, 2′‐bithiophene (2T), thieno[3, 2‐ b ]thiophene (TT), and 3, 3′‐difluoro‐2, 2′‐bithiophene (2F2T) donor units, respectively. PNTDT‐2F2T exhibits superior polymer crystallinity and a much higher absorption coefficient than those of PNTDT‐2T or PNTDT‐TT because of adequate matching between highly coplanar A (NTDT) and D (2F2T) building blocks. A bulk heterojunction solar cell based on PNTDT‐2F2T exhibits a power conversion efficiency of up to 9.63%, with a high short circuit current of 18.80 mA cm −2 and fill factor of 0.70, when a thick active layer (>200 nm) is used, without postfabrication hot processing. The findings demonstrate that the polymer crystallinity and absorption coefficient can be effectively controlled by selecting appropriate D and A building blocks, and that NTDT is a novel and versatile A building block for highly efficient thick‐active‐layer PSCs. Abstract : A novel 1, 5‐naphthyridine‐2, 6‐dione‐based conjugated polymer is developed and applied as a donor in the active layers of efficient polymer solar cells. PNTDT‐2F2T exhibits outstanding polymer crystallinity and absorption coefficient. A polymer solar cell device made using PNTDT‐2F2T exhibits a high power conversion efficiency (9.63%) with a thick active layer (>200 nm).